APLIKASI BERBASIS ANDROID TEST OF ENGLISH FOR INTERNATIONAL COMMUNICATION (TOEIC) UNTUK PEMBELAJARAN - Alexander Dharmawan (LPPM Poltek ST Paul, 2022)
English is an international language. English is used as the language of communication all over the world. With conditions like this, everyone who wants to progress is required to be able to speak English. There are already many foreign companies operating in Indonesia. However, English is not an official language in Indonesia, so their mastery is not as good as those who use English as the official language of the country. For that we need an English learning application that can help students of Madrasah Aliyah Negeri 1 Magelang in studying the Test Of English for International Communication (TOEIC). TOEIC is an international standard test that is used to measure a person's ability to speak English in communicating in the world of work. System development will be carried out using the spiral method and system design will be carried out using a modeling language using UML (Unified Modeling Language). While the programming used is java using the MySQL database, android studio to create applications with the android technology. The final result of the implementation produces an Android-based application in the form of TOEIC learning media that can be used by students anywhere, not only in class and can be repeated, so that English language skills will increase.